2005
DOI: 10.1016/j.jcrs.2005.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Patient pain during stretching of small pupils in phacoemulsification performed using topical anesthesia

Abstract: Pupil stretching during phacoemulsification in patients with small pupils was performed with minimal patient-reported pain using topical anesthesia. Stretching small pupils with a mechanical device during phacoemulsification performed under topical anesthesia was a safe procedure and did not result in significant patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…23,24 Topical anaesthesia does not block all pain fibers from the iris and ciliary body, so manipulation of the iris might be expected to cause pain. 25 As we know, some manipulations performed during phacoemulsification cause significant levels of pain. O'Brien et al 1 showed that hydrodissection, phacoemulsification, lens aspiration, and intraocular lens insertion require the most manipulation of the iris and were associated with higher pain scores during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Topical anaesthesia does not block all pain fibers from the iris and ciliary body, so manipulation of the iris might be expected to cause pain. 25 As we know, some manipulations performed during phacoemulsification cause significant levels of pain. O'Brien et al 1 showed that hydrodissection, phacoemulsification, lens aspiration, and intraocular lens insertion require the most manipulation of the iris and were associated with higher pain scores during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that the adult retina forms appropriately during development, RPCs transition through states of developmental competence by coordinating cell cycle exit and cell fate specification to generate an ordered array of uniquely fated cell populations (Dyer and Cepko 2001;Fujita 2003;Pearson and Doe 2004;Zhang et al 2004;Kageyama et al 2005). When these processes are disrupted, as observed in some cases of human microphthalmia and anophthalmia (Zigman and Paxhia 1988;Loosli et al 1998;Fantes et al 2003;Driver et al 2005;Fitzpatrick and van Heyningen 2005;Labadie et al 2005;O'Brien et al 2005;Ragge et al 2005a,b;Xu et al 2005), vision is severely compromised. Identifying the molecular mechanisms that allow some progenitors to continually divide yet promote neighboring cells to stop dividing and differentiate at appropriate times during development is pivotal to the understanding of both normal and defective retinal development.…”
mentioning
confidence: 99%
“…All procedures were performed using topical anesthesia. 10 , 11 In addition, 0.5% tetracaine hydrochloride (Tetracaine; Cooper Pharmaceutical SA) drops were instilled.…”
Section: Methodsmentioning
confidence: 99%